Aphasia-friendly medication instructions: effects on comprehension in persons with and without aphasia. Issue 3 (4th March 2022) - Saylor, Anna; Wallace, Sarah E.; Brown, Elena Donoso; Schreiber, James
ABSTRACT: Background: Written medication instructions provide critical information but are often presented at high reading levels resulting in poor comprehension. Comprehension of written health information can be particularly difficult for people with language impairments, such as aphasia. Methods & Procedures: Nine people with aphasia (PWA) and nine people without aphasia (PWoA) participated in this study. Each participant reviewed two unmodified medication instructions and two modified medication instructions using aphasia-friendly principles, then answered eight multiple-choice questions and provided their preferences. Outcomes & Results: Results showed that PWA demonstrated improved comprehension given modifications, but PWoA's comprehension did not significantly improve with modifications. Group comparison in the modified condition demonstrated that PWoA still demonstrated significantly higher comprehension compared to PWA. Most participants, in both groups, preferred aphasia-friendly instructions compared to the unmodified instructions. Conclusions: This study highlights the need for improvements in healthcare information to support comprehension and independence of all persons with regard to readability of complex health information.